Homolytic versus Heterolytic Hydrogen Evolution Reaction Steered by a Steric Effect. (24th March 2020) - Guo, Xiaojun; Wang, Ni; Li, Xialiang; Zhang, Zongyao; Zhao, Jianping; Ren, Wanjie; Ding, Shuping; Xu, Gelun; Li, Jianfeng; Apfel, Ulf‐Peter; Zhang, Wei; Cao, Rui
Abstract: Several H−H bond forming pathways have been proposed for the hydrogen evolution reaction (HER). Revealing these HER mechanisms is of fundamental importance for the rational design of catalysts and is also extremely challenging. Now, an unparalleled example of switching between homolytic and heterolytic HER mechanisms is reported. Three nickel(II) porphyrins were designed and synthesized with distinct steric effects by introducing bulky amido moieties to ortho‐ or para‐positions of the meso‐phenyl groups. These porphyrins exhibited different catalytic HER behaviors. For these Ni porphyrins, although their 1e‐reduced forms are active to reduce trifluoroacetic acid, the resulting Ni hydrides (depending on the steric effects of porphyrin rings) have different pathways to make H2 . Understanding HER processes, especially controllable switching between homolytic and heterolytic H−H bond formation pathways through molecular engineering, is unprecedented in electrocatalysis. Abstract : Ni porphyrins with distinct steric effects by introducing amido units to ortho ‐ or para ‐positions of meso ‐phenyl groups display different catalytic HER behaviors. Depending on steric resistance on both sides of porphyrin rings, hydride intermediates, formed through the oxidative protonation of 1e‐reduced Ni porphyrins, either undergo bimetallic homolysis or are further reduced for heterolytic protonolysis to evolve H2 .